Forever and For Always (The Inn at Sunset Harbor-Book 2) - Sophie, Love (Lukeman Literary, 2016)
"Sophie Love's ability to impart magic to her readers is exquisitely wrought in powerfully evocative phrases and descriptions....FOR NOW AND FOREVER is the perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (Diane Donovan) "A very well written novel, describing the struggle of a woman (Emily) to find her true identity. The author did an amazing job with the creation of the characters and her description of the environment. The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews, Roberto Mattos (re For Now and Forever) FOREVER AND FOR ALWAYS is book #2 in the romance series THE INN AT SUNSET HARBOR, which begins with book #1, FOR NOW AND FOREVER-a free download! 35 year old Emily Mitchell has fled her job, apartment and ex-boyfriend in New York City for her father's abandoned home on the coast of Maine, needing a change in her life. Tapping her life savings to restore the historic home, and with a budding relationship with the caretaker, Daniel, Emily prepares to open the Inn at Sunset Harbor as Memorial Day comes. But all does not go as planned. Emily learns quickly that she has no idea how to run a B&B. The house, despite her efforts, needs new, urgent repairs she cannot afford. Her covetous neighbor is still determined to make trouble for her. And worst of all: just as her relationship with Daniel is blossoming, she learns he has a secret. One which will change everything. With her friends urging her to return to New York City and her ex-boyfriend trying to win her back, Emily has a life-changing decision to make. Will she try to stick it out, to embrace small-town life, her father's old house? Or will she turn her back on her new friends, neighbors and life-and on the man she has fallen in love with? FOREVER AND FOR ALWAYS is book #2 of a dazzling new romance series that will make you laugh, make you cry, will keep you turning pages late into the night-and will make you fall in love with romance all over again. Book #3 will be available soon.
Keywords: Romantika, romány pro ženy